New species and key of Aeletes Horn (Coleoptera: Histeridae: Abraeinae) from Brazil - Leivas, Fernando W.t.; Mise, Kleber M.; Almeida, Lúcia M.; Macari, Bruna P.; Gomy, Yves (Zootaxa, 2012)
A new species of abraeine histerid, Aeletes (s. str.) nicolasi sp. nov. is described and illustrated from Paraná State, Brazil.An identification key is provided to the known Brazilian species of Aeletes. Ecological data are provided for the new species and for the genus, being the first record of Aeletes in carrion.